Study abroad and second language use : - Aveni, Valerie A Pellegrino (Cambridge University Press, 2005)
Limitations in linguistic and cultural knowledge make self-presentation a more difficult task when we interact in a new language in a foreign country. This volume explores the problems faced by language students embarking on "study abroad" programs by considering factors that complicate self-presentation and how students overcome them. The book's insight makes it an invaluable resource for professionals in second language acquisition, and for teachers and students preparing for study abroad.